Zinowiewia sebastianii (Celastraceae), a new high-Andean species from the Colombian Eastern Cordillera - Favio Antonio Gonzalez Garavito; Luis Roberto Sánchez Montaño (Caldasia)
Zinowiewia sebastianii, a new species from high-Andean forests of the Eastern Cordillera at the department of Boyacá (Colombia) is described and illustrated, and its taxonomic affinities are discussed. Individuals of the new species are shrubs to 5 m tall, with interpetiolar, laciniate stipules, leaf blades with 8–11 pairs of lateral veins and entire, plane margin, 2-forked dichasia to 1 × 1 cm, axillary to the distal leaves, calyx, corolla and androecium pentamerous or tetramerous, and two-celled, one-seeded samaras 18–20 × 5–7 mm. Based on the low number of individuals of Z. sebastianii observed within an area of occupancy < 10 km2, in severely fragmented forests, the species is proposed as Critically Endangered (CR), as it faces an extremely high risk of extinction in the wild.